2007
DOI: 10.1111/j.1365-294x.2007.03381.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical and ecological determinants of genetic structure in arctic canids

Abstract: Wolves (Canis lupus) and arctic foxes (Alopex lagopus) are the only canid species found throughout the mainland tundra and arctic islands of North America. Contrasting evolutionary histories, and the contemporary ecology of each species, have combined to produce their divergent population genetic characteristics. Arctic foxes are more variable than wolves, and both island and mainland fox populations possess similarly high microsatellite variation. These differences result from larger effective population size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
141
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 88 publications
19
141
3
2
Order By: Relevance
“…There have also been a number of recent landscape genetic studies that have shown that dispersal in carnivore species can be habitat specific, that is, individuals have a tendency to disperse preferentially into habitat similar to their natal one (Pilot et al, 2006;Carmichael et al, 2007;Musiani et al, 2007). These studies found a good concordance between geographical boundaries of genetic clusters and ecological factors such as climate and habitat types, as well as diet composition and distribution of prey.…”
Section: Discussionmentioning
confidence: 64%
“…There have also been a number of recent landscape genetic studies that have shown that dispersal in carnivore species can be habitat specific, that is, individuals have a tendency to disperse preferentially into habitat similar to their natal one (Pilot et al, 2006;Carmichael et al, 2007;Musiani et al, 2007). These studies found a good concordance between geographical boundaries of genetic clusters and ecological factors such as climate and habitat types, as well as diet composition and distribution of prey.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies using both mitochondrial and microsatellite markers have demonstrated that the presence of sea ice is the most important factor in explaining arctic fox global population structure [17 -19]. Genetic differentiation between North America, north Greenland and Svalbard is low, implying extensive movement across the sea ice between these areas [17,20]. In fact, the genetic proximity of these areas to Siberia has prompted suggestions that Svalbard may act as a central junction for gene flow across the entire Arctic, mediated by sea ice [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Preferential dispersal towards a habitat similar to one of juvenile life [16] can generate and maintain evolutionary divergence in highly mobile species. While this process may be 'imprinted' in turtles or fishes [17], social learning of foraging techniques for particular prey or habitat may influence dispersal in species having long-term bonds between mothers and calves [4,15]. Individuals may therefore have higher foraging success in familiar habitats where they can use learned hunting techniques, which might enhance their fitness.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of influence of historical versus current processes on population structure can vary among species [13,14] and both can have an important role. For example, genetic differentiation patterns of arctic canids might be linked to historical climatic conditions, social structure and dispersal behaviours [15]. Preferential dispersal towards a habitat similar to one of juvenile life [16] can generate and maintain evolutionary divergence in highly mobile species.…”
Section: Introductionmentioning
confidence: 99%